ECOLOGICALLY SAFE SYSTEM OF WATER MANAGEMENT PRODUCTION FROM MULTICOMPONENT METAL-WASTEWATER - , В. Л. (Municipal economy of cities. Series: «Economy science», 2013)
We consider a closed system of water management industries with wastewater, containing heavy metals, organic contaminants and mineral salts.